Parasitic Nematodes of Tropical Megascolecid Earthworm Pheretima leucocirca from Ba Vi National Park in Viet Nam - Spiridonov, S.E.; Ivanova, E.S. (Вестник зоологии, 1998)
Representatives of several genera of drilonematid and thelastomatid nematodes including one new species of Iponema, two new species of Homungella, two new species of Siconema, one new species of Travassosinema and one new species of Posterovulva are described from the body cavity and intestinal lumen of tropical megascolecid earthworms Pheretima leucocirca collected on the Ba Vi mountain near Hanoi, Viet Nam.